Determinants of liquidity in commercial banks: Evidence from the Turkish banking sector - Ahmet Karakaş; Melek Acar Boyacioğlu (CES Working Papers, 2022)
Liquidity management has an important place in the asset and liability management of banks. The aim of this study is to empirically investigate the intra-bank and macroeconomic factors that affect liquidity in 20 Turkish commercial banks. Financial data of commercial banks operating in the 2002- 2022 period and macroeconomic data for the same period are taken into account. In the panel data analysis where liquidity ratios liquid asset ratio (LAR), acid-test ratio (ATR) and current ratio (CR) were taken as dependent variables, a negative relationship between liquidity ratios and deposits to liabilities ratio (DR), financial asset ratio (FAR), fixed asset ratio (FIXR), economic growth rate (gross domestic products - GDP), central bank interest rate (INT), loans to assets ratio (LR), net interest margin (NIM), non-performing loans ratio (NPL); a positive correlation with liquidity ratios and equity ratio (equities to assets ratio, CAP), inflation rate (INF), natural logarithm of asset size (TA), foreign exchange rate (XR) was found. In the study, no statistically significant relationship was found between foreign exchange liquidity ratio (FXLR) and liquidity ratios. Despite its profitability- reducing effect, banks need to manage their liquidity sensitively and effectively in order to maintain the trust of customers and market, especially during crisis periods.
Keywords: 330; commercial banking; liquidity; Turkey